Pengaruh e-book pengayaan fisika disertai tugas berita dan fakta terhadap keterampilan berpikir kritis dan kreatif peserta didik kelas X SMAN 2 Padang - Riolin Putri Artiwi; Asrizal Asrizal Asrizal; Desnita Desnita Desnita; Yenni Darvina Yenni (Universitas Negeri Padang, 2020)
Achievement of student learning outcomes in learning Physics is still not as expected. The reason is there are several factors such as the lack of books as learning resources that support students' knowledge and insights beyond the knowledge taught in school. Like an enrichment book, which contains facts about learning so that it helps students better understand learning. In addition, there is no electrical book (E-Book) as the use of technology in science to support learning activities that have an impact on student learning outcomes. Therefore, speculation the solution to this problem is the giving of Motion Theme Physics Enrichment E-Books to students of SMAN 2 Padang. This study aims to determine the effect and relationship of E-Book Enrichment of Motion Theme Physics on Student Learning Outcomes Class X of SMAN 2 Padang.The type of research applied was quasi-experimental research with the research scheme Posttest Only Control Group Design. The population in this studys were all students of class X SMAN 2 Padang who were register in the 2019/2020 Academic Year. Sampling for research is done by combining purposive sampling and cluster random sampling techniques. The sample in this study were 72 students from class X MIPA 2 as an experimental class and class X MIPA 3 as a control class. The research instrument consisted of a demonstration assessment sheet of critical thinking skills and creative thinking skills. The data in this study were analyzed using descriptive analysis and two average similarity tests.The results showed that there was an influence on student learning outcomes which was significant from the giving of the Motion Theme Physics Enrichment E-Book and there was a significant correlation of the giving of the Motion Theme Physics Enrichment E-Book to student learning outcomes for knowledge and skill competencies at the 0.05 level. It can be seen in the analysis of the data, that for knowledge competencies and skills the value of th is in the rejection area of Ho which means that student learning outcomes experience significant differences for the two competencies.